Seasonal and spatial variations of nutrients and environmental effects under anthropogenic influence in Daya Bay, China - Zhao, Jincheng; He, Jiawei; Li, Cai; Yang, Zeming; Liu, Cong; Zhang, Xianqing; Qin, Min; Tang, Dejing; Zhou, Wen; Xu, Zhantang; Cheng, Yuanyue (Frontiers in Marine Science, 2025)
Nutrients are crucial factors for the growth of phytoplankton, and their biogeochemical processes directly impact marine biodiversity. In this study, based on two cruise observations in spring and summer of 2024, the seasonal and spatial variations of nutrients, chlorophyll a, and other ecological indicators in Daya Bay were explored. The results indicated that the average concentrations of dissolved inorganic nitrogen and silicate were 3.61 ± 3.99 µM and 26.27 ± 13.91 µM in summer, respectively, compared with 2.48 ± 1.53 µM and 23.8 ± 6.77 µM in spring. The average concentration of dissolved inorganic phosphate was 0.29 ± 0.12 µM in summer, lower than 0.32 ± 0.09 µM in spring. The stoichiometric proportion among nutrients at most monitoring stations were far from Redfield ratio, and a succession from N-limited to P-limited was observed. A transformation has been observed in the dominant composition of dissolved inorganic nitrogen, shifting from ammonia to total oxidized nitrogen as the main component, which is mainly attributable to the decrease in aquaculture activities in Daya Bay over the last 3 years. In addition, the warm wastewater discharge from nuclear power stations directly influences the distribution of phytoplankton in the surrounding areas. This study provides timely information regarding recent shifts in ecological indicators and is significant to the ecological protection, environmental management, and policy adjustment in Daya Bay.